Imaging with laser photography camera during limited visibility - Zarzycki, Mikołaj; Piszczek, Marek; Rutyna, Krzysztof; Kowalski, Marcin; Karol, Mateusz; Szustakowski, Mieczysław (Photonics Letters of Poland, 2014)
Present systems for vision monitoring very often employ many different imaging devices working in various spectral ranges e.g. visible (VIS), near infrared (NIR), infrared (IR). Every single spectral range delivers slightly different relevant information for process of threats detection, recognition and identification. However, technology progress still does not satisfy every need. Finding new vision solutions, capable for imaging in very difficult conditions (adverse weather conditions, partial occultation of observed scene) is still one of the most urgent and demanding task for researchers. One of the possible solutions is using a camera working with time-spatial framing method. This method is able to minimize the impact of adverse factors on image acquisition process. Laser photography device (LPD) is a camera developed in the Institute of Optoelectronics, Military University of Technology working according to the time-spatial framing method. The paper presents theoretical basics and initial results of the laser photography device tests. Full Text: PDF References L. Michalski, K. Eckersdorf, J. Kucharski, Termometria – przyrządy i metody (Wydawnictwo Politechniki Łódzkiej, Łódź 1998). K. Chrzanowski, K. Firmanty, J. Bareła, Krótkofalowe kamery podczerwieni (Pomiary Automatyka Robotyka 7-8/2005). M. Piszczek, K. Rutyna, M. Szustakowski, "Imaging of space with using optoelectronic observation system with active illumination", Europ. Phys. J.: Special Topics 154(1), 153 (2008). CrossRef M. Piszczek, M. Kowalski, M. Szustakowski, K. Rutyna, K. Ludwikowski, "The Role of a Laser Photography Device Illuminator in Acquisition of Spatial Information", Acta Phys. Pol. A 122(5), 862 (2012). DirectLink M. Piszczek, K. Rutyna, Rejestracja obrazów metodą kadrowania czasoprzestrzennego (Pomiary Automatyka Kontrola 53, nr 9bis/2007). M. Piszczek, K. Rutyna, Roczniki geomatyki, Tom VI Zeszyt 7, 73 (2009). M. Piszczek, M. Zarzycki, "Możliwość zastosowania elementów rozszerzonej rzeczywistości w urządzeniu fotografii laserowej", Elektronika 10, 22 (2012).